Does the Sharia Personal Financial Management Require? Study of Sharia Financial Literacy Among Lecturers - Setyawati, Irma; Suroso, Sugeng (International Journal of Economics and Financial Issues, 2017)
The purpose of this study was to analyze some of the critical factors in the socioeconomic variables that influence the sharia personal financial management. This research used a verification analysis. Verification analysis using logistic regression to determine the influence of socioeconomic, sharia financial literacy and personal financial management variables. Research on personal finance management is not much to do on the lecturer as a respondent, but uses the student as respondents. Therefore, teachers or lecturers as a party to impart knowledge to students, it is important to know how their personal financial management skills. Keywords: financial knowledge; financial behaviors; financial attitudes; sharia financial literacy; sharia personal financial management JEL Classifications: D22, G02